An Islamic Caliphate in Sahel? Similarities and Differences between Daesh Territorial Expansion in Irak and the Consolidation of Jihadi Groups in Mali (Comillas Journal of International Relations, 2020)
This article compares the Iraqi political, social and historic conditions existing in the moment of Daesh expansion with the current political, social and historic conditions in the Malian State. In order to conduct the analysis, John M. Berger extremist model, the sociologic theories supporting it and other theories about the presence of international powers, are employed. This model enables to assess how group identities have been forged in Iraq and Mali, how they have entered in conflict patronized by international powers and how the jihadi groups have taken advantage from the intergroup conflict to increase its members, legitimate themselves as a group while expanding through a territory in the Iraqi case. Similarities and differences are established between the Iraqi and Mali cases in order to determine whether a new territorial expansion, similar to the one Daesh headed in Iraq and led by jihadi groups, could take place inside the Malian territory.
Keywords: intergroup conflict; identity; legitimacy; rhetoric; statu quo